Does comorbid disruptive behavior modify the effects of atomoxetine on ADHD symptoms as measured by a continuous performance test and a motion tracking device? - Wehmeier, Peter M.; Banaschewski, Tobias; Dittmann, Ralf (Journal of attention disorders, 2015)
Objective: To compare the reduction of ADHD symptoms under atomoxetine in patients with and without comorbid oppositional defiant disorder (ODD) or conduct disorder (CD) using a computer-based continuous performance test (cb-CPT) combined with an infrared motion tracking (MT) device. Method: Secondary analysis of a placebo-controlled study in ADHD patients (6-12 years old) treated with atomoxetine (target dose: 1.2 mg/kg per day). Cb-CPT/MT scores were analyzed using ANCOVA (last observation carried forward [LOCF]). Results: The data (N = 125) suggested a more pronounced atomoxetine effect in the group with comorbid ODD/CD as measured by all cb-CPT/MT parameters except for “normalized variation of reaction time” (nVRT). Conclusion: The results showed that atomoxetine reduced ADHD severity as measured by cb-CPT and MT parameters regardless of whether comorbid ODD/CD was present. The treatment effect of atomoxetine on hyperactivity appears to be more pronounced in the subgroup of patients with comorbid ODD/CD than in the subgroup without this comorbidity.